Ethnonationalist conflict in postcommunist states : varieties of governance in Bulgaria, Macedonia, and Kosovo - Koinova, Maria (National and ethnic conflict in the 21st century., 2013)
Tracing the development of informally institutionalized conflict dynamics in Bulgaria, Macedonia, and Kosovo, Maria Koinova analyzes why some conflicts were resolved with minimal violence after the end of communism and others broke out into civil war.